On the optimal reconstruction of the values of operators - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a continuous operator $А:\; X → Y,$ we formulate the problem of the optimal renewal of values $Аx,\; x \in X$ by decreasing the uncertainty domain by using an information $μ_k(x),\; k = 1, 2, ...,$, where $μ_k$ are continuous functionals, defined on the space $X$. Specific results are obtained for some integral operators in functional spaces.